IMPLEMENTASI PENDIDIKAN INKLUSI DI SDN KALICARI 02: STUDI KASUS - Roshida, Elviana; Fajriyah, Khusnul; Siswanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Inclusive education represents an effort to enhance the quality of educational services, ensuring equity and alignment with inclusive education principles. It is an educational approach that provides students with special needs the opportunity to learn alongside their peers in mainstream schools, with educational services tailored to each student's individual requirements. Through inclusive education, students with special needs not only exercise their right to learn but also gain opportunities to develop academic, social, and independent living skills—assets that serve them well in society. This study aims to describe the implementation of inclusive education at SDN Kalicari 02, identify the obstacles faced during this process, and outline the efforts made by the school and teachers to overcome these challenges. A qualitative approach utilizing a case study method was employed. The findings indicate that inclusive education has been implemented through non-discriminatory student admission, the adaptation of instructional services, and collaboration with parents. Challenges encountered include limited school resources, the diverse characteristics of students with special needs, and a lack of optimal support from some parents. Efforts to address these issues include enhancing teacher competence, tailoring instruction to the abilities of students with special needs, and strengthening communication with parents. The implementation of inclusive education at SDN Kalicari 02 has proceeded adaptively, as the school successfully aligns educational services with student needs and the school's own conditions. However, the implementation cannot yet be considered fully effective due to persistent obstacles, such as the unavailability of Special Support Teachers (GPK). Keywords: Case Study, Inclusive Education Implementation, ABK